Association of early childhood constipation with the risk of autism spectrum disorder in Taiwan: Real-world evidence from a nationwide population-based cohort study - Lee, Yi-Feng; Wu, Meng-Che; Ma, Kevin Sheng-Kai; Huang, Jing-Yang; Wei, James Cheng-Chung (Frontiers in Psychiatry, 2023)
Background Autism spectrum disorder (ASD) is a neurodevelopmental problem that presents with limited interests, repetitive behaviors, and deficits in reciprocal communication and social interactions. Mounting evidence indicates that an imbalanced gut microbiota contributes to autism via the gut-brain axis. Constipation may result in alteration of the gut microbiota. The clinical influence of constipation on ASD has not been fully researched. Thus, in this study we aimed to evaluate whether early childhood constipation influenced the risk of developing ASD using a nationwide population-based cohort study. Methods We identified 12,935 constipated children aged 3 years or younger from the National Health Insurance Research Database (NHIRD) in Taiwan from 1997 to 2013. Non-constipated children were also selected from the database and propensity score matching of age, gender, and underlying comorbidities was conducted with a ratio of 1:1. Kaplan-Meier analysis was applied to determine different levels of constipation severity and cumulative incidence of autism. Subgroup analysis was also applied in this study. Results The incidence of ASD was 12.36 per 100,000 person-months in the constipation group, which was higher than the rate of 7.84 per 100,000 person-months noted in the non-constipation controls. Constipated children had a significantly higher risk of autism when compared to the non-constipation group (crude relative risk = 1.458, 95% CI = 1.116-1.904; adjusted hazard ratio = 1.445, 95% CI=1.095-1.907). Moreover, among constipated children, a higher number of laxative prescriptions, male gender, constipation during infancy, and atopic dermatitis were significantly associated with higher risks of ASD when compared to the non-constipation group. Conclusion Constipation in early childhood was correlated with a significantly increased risk of ASD. Clinicians should pay attention to the possibility of ASD in constipated children. Further research is necessary to study the possible pathophysiological mechanisms of this association.